Open Wave Height Logger: An open source pressure sensor data logger for wave measurement. (8th June 2020) - Lyman, Theodore P.; Elsmore, Kristen; Gaylord, Brian; Byrnes, Jarrett E. K.; Miller, Luke P.
Abstract: Wave‐generated flows, associated hydrodynamic forces, and disturbances created by them play critical roles in determining the structure and health of near‐shore coastal ecosystems. Oscillatory motions produced by waves increase delivery of nutrients and food to benthic organisms, and can enhance vertical mixing to facilitate delivery of larvae and spores to the seafloor. At the same time, wave disturbances can remove individuals and biomass with far‐reaching effects on critical coastal ecosystems and the biodiversity within them. Commercial instruments designed to measure wave characteristics and the effects of wave energy can be expensive to purchase and deploy, limiting their use in large quantities or in areas where they may be lost. We have developed an inexpensive open‐source pressure transducer data logger based on an Arduino microcontroller that can be used to characterize wave conditions for deployments lasting multiple months. Our design criteria centered around simplicity, longevity, low cost, and ease of use for researchers. Housed in ubiquitous polyvinylchloride (PVC) plumbing and constructed primarily with readily available materials, the Open Wave Height Logger (OWHL) can be fabricated in a college setting with basic shop tools. The OWHL performs comparably to commercial pressure‐based wave height data loggers during tests in the field, creating the opportunity to expand the use of these sensors for applications where sufficient spatial replication or risk of instrument loss would otherwise be cost prohibitive.